IMPLEMENTASI MODEL CTL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKN MATERI HAM DI KELAS V MI AL-IKHLAS BANJARGONDANG 1 - Maryanto, Hafiid Misbakhul; Anwar, Moh. Farid Nurul; Rozhana, Kardiana Metha (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study aims to improve students' learning outcomes in the subject of Civic Education (PKn), particularly on the topic of Human Rights (HAM), which has often posed challenges at the elementary school level due to students’ low comprehension. The Contextual Teaching and Learning (CTL) model was implemented to connect learning materials with students’ real-life experiences. This research employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which includes four stages: planning, action, observation, and reflection, conducted over two cycles. Data were collected through observation, learning outcome tests, and documentation. The data were analyzed using descriptive quantitative analysis to evaluate the improvement in learning outcomes based on the number of students meeting the Minimum Mastery Criteria (KKM). The results showed a significant increase, with 12 out of 17 students (70.59%) achieving the KKM in the first cycle, and 16 students (94.12%) in the second cycle. These findings indicate that the CTL model effectively enhances students’ learning outcomes by helping them relate the concept of human rights to their daily lives. CTL can serve as an innovative alternative teaching strategy for Civic Education at the elementary level. The researcher recommends the continuous application of the CTL model and further development of varied contextual learning materials to achieve more optimal outcomes.